Rubber and the Making of Vietnam : An Ecological History, 1897-1975 - Aso, Michitake (Book collections on Project MUSE., 2018)
In this ground breaking study, Michitake Aso narrates how rubber plantations came to dominate the material and symbolic landscape of Vietnam and its neighbours, structuring the region's environment of conflict and violence. Aso demonstrates how postcolonial socialist visions of agriculture and medicine were informed by their colonial and capitalist predecessors in important ways.